Sustainable Careers within Greening Economies - Hopner V; Carr S; Wloch J (Australian Council for Educational Research for SAGE Publications, 2024)
Sustainable Livelihoods are more adaptable than precarious jobs, for career development through Decent Work. An essential element for Career Sustainability is Climate action, that includes Just Transitions from carbon-intensive to carbon-neutral or regenerative work. This paper analyses a municipal transition from coal-mining to a more carbon-neutral, city economy, which has foregrounded just transition for miners, and improved the wider ecosystem. The Polish city of Katowice in Poland illustrates how work and career structures, in this case municipal, can work for people in everyday life and their future careers. The case may also serve as a lighthouse project for future just transitions, as part of sustainable career development, by greening economies and supporting access to decent work for all.
Keywords: Sustainable livelihoods; sustainable career; sustainable development; decent work; SDGs; climate action